Design and development of material handling equipment for cordierite slab. (2021) - Senthil Gavaskar, S.; Devan, P.K.; Bibin, Chidambaranathan; Ashok, Kovuru; Mariselvan, M.; Mohamed Akram, A.; Panneerselvam, P.
Abstract: The material handling equipment assures the convenient conveyance of the required quantity of material at the desired restriction with the lowest cost and greater security. Due to the steady development of new technology over material handling machinery is witnessing continuous automation. The problem occurs when turning the soft material like cordierite ceramic material before the fire in the kilns. The soft surfaces experience fractures that are often difficult to see naked eye during spinning. A bat for kiln must bear the turned product. By using a clamping lot, the stock would be turned. The material of two ratchet belt carries a product using two clamps.